EKSTRASI SENYAWA ANTIBAKTERI DARI DIATOM CHAETOCEROS GRACILIS DENGAN BERBAGAI METODE - Setyaningsih, Iriani; Hardjito, Linawati; Monintja, Daniel R.; Sondita, M. Fedi A.; Bintang, Maria; Lailati, Nispi; Panggabean, Lily (JURNAL BIOLOGI INDONESIA, 2008)
ABSTRACTExtraction of Antibacterial Compound from Diatom Chaetoceros gracilis WithDifferent Methods. Diatom is phytoplankton which is commonly found in off shore.Chaetoceros produce antibacterial which inhibit some bacteria. This research was donein 3 steps. At first, Chaetoceros gracilis was cultivated in temperate controlled roomwith lighting 24 hours. The culture was harvested on 14 days, then it was dried andweighted. The second step, biomass was disrupted by different method such as sonicator,glass beads, and undisrupting. Then the biomass was maserated, filtrated, and evaporated.The crude extracts were tested to pathogen bacterial. The third step, the extraction wasconducted using hexana (non polar solvent), ethyl acetate (semi polar solvent), andmethanol (polar solvent). The crude extracts were tested to the pathogenic bacteria.The result showed that the produce cell disruption antibacterial activity by sonicator.The biggest inhibition zone was obtained by hexana but produced lower yield.Key words: Chaetoceros gracilis, growth, extraction, disrupting, antibacteria